A Rare Case of Solitary Enchondroma of Distal End of Radius Diagnosed Retrospectively. (International Journal of Biomedical Research, 2014)
Introduction: Solitary enchondroma of distal end of radius is extremely rare. Even after extensive search very little regarding it was found in the literature (even after extensive search only two case reports were found). This case being one of its kind as the diagnosis was done retrospectively as all the preoperative investigations pointed on different diagnosis so worthy of reporting. Case Report: A 15- year-old female presented with pain in the right distal forearm for about 12 weeks with no associated constitutional symptoms. Preliminary investigations including MRI scan were suggestive of Chronic Osteomyeltis, therefore curettage was done. Histopathological examination report came as solitary enchondroma of distal radius, which is extremely rare ( 1% incidence). Patient was symptom free with no evidence of recurrence at the follow-up of one year. Conclusion: The common differential diagnosis of a lytic lesion of distal radius in this age group includes Osteomyelitis, aneurysmal bone cyst, chondromyxoid fibroma, non-ossifying fibroma. Distal Radius is a very rare location for a solitary enchondroma but as our case signifies enchondroma should be kept as a differential diagnosis while evaluating lytic lesion of distal Radius.